Single nucleotide polymorphism rs110861313 in the intergenic region of chromosome 23 is associated with the development of leukosis in the Russian Black Pied cattle - R. B. Aitnazarov; E. V. Ignatieva; T. A. Agarkova; N. G. Dvoeglazov; N. A. Osipova; V. V. Khramtsov; N. S. Yudin (Вавиловский журнал генетики и селекции)
In recent years, using a genome-wide association study (GWAS), a number of single nucleotide polymorphisms (SNPs) have been suggested to be associated with susceptibility to leukemia in cattle. However, all studies have been done with purebred Holstein cows and their hybrids. In this regard, it is important to confirm the functional role of polymorphisms previously identified in a GWAS study in Russian cattle breeds. The aim of this study was to verify the association between rs110861313 in the intergenic region of bovine chromosome 23 and leukemia in the Russian Black Pied cattle. Based on the levels of bovine leukemia virus (BLV)-specific antibodies detected in serum using serodiagnostic techniques, animals were divided into three groups: healthy animals (n = 115), asymptomatic virus carriers (n = 145) and animals with leukemia (n = 107). Genotyping of rs110861313 was carried out using polymerase chain reaction followed by analysis of restriction fragment length polymorphisms. A significant decrease in the frequency of the A/A genotype (11.2 %) was revealed in animals with persistent lymphocytosis compared to virus carriers (27.6 %) (p < 0.002). At the same time, the frequency of animals with the C/C genotype in animals with persistent lymphocytosis (41.1 %) was significantly higher than that of virus carriers (21.4 %) (p < 0.001). In this case, asymptomatic virus carriers can be considered a more suitable control than healthy animals that have not been in contact with the virus. According to bioinformatics analysis, resistance to BLV can be due to the presence of the transcription factor FOXM1 binding site in the region of rs110861313. FOXM1 is expressed in immune cells and can potentially affect the expression of the neighboring genes (LY6G5B, GPANK1, ABHD16A, LY6G6F, LY6G6E, CSNK2B, ApoM). Thus, we found that SNP rs110861313 in the intergenic region of bovine chromosome 23 is associated with the development of leukemia following BLV infection in the Russian Black Pied cattle.